The Impact of Liquidity and Corporate Efficiency on Profitability - Thuy Thi Cam Nguyen; Anh Thi Hong Le; Cong Van Nguyen (Ital Publication, 2024)
This study aims to investigate and determine the trend and extent of the impact of a company's liquidity and efficiency on profitability. Research data is collected on the audited financial statements of Vietnam's top 100 listed companies. Regression models (pooled OLS, FEM, and REM) and necessary tests are used to select the appropriate analysis model. Model defects are overcome by GLS regression. The research results confirm the strong, positive impact of liquidity, company efficiency, and company growth rate on profitability. In addition, the research results also demonstrate a significant negative impact between financial leverage and profitability. This article is the first study to simultaneously address the effects of liquidity and corporate efficiency on profitability. Furthermore, it is the first empirical study applying GLS regression to analyze the impact of liquidity and corporate efficiency on the top 100 listed companies in the Vietnamese market. This market provides an ideal analytical framework because of its heterogeneity in terms of its history of origin and development and its political, cultural, social, and governance characteristics. To make the research results more general, future studies can expand the scope of the survey to all companies listed on the stock market. Doi: 10.28991/ESJ-2024-08-01-013 Full Text: PDF